Young People Under Youth Justice Supervision With Varying Child Protection Histories: An Analysis of Group Differences. (February 2019) - Malvaso, Catia G.; Delfabbro, Paul H.; Day, Andrew; Nobes, Gavin
There is now convincing evidence that childhood maltreatment is associated with youth offending; however, relatively little is known about the characteristics and needs of those who are involved in both the child protection and youth justice systems, and the extent to which these might differ according to level of child protection involvement. This study reports the characteristics and needs of 2, 045 young people who were under supervision in secure custody or detention in South Australia between 1995 and 2012 according to the level of exposure to the child protection system in an Australian jurisdiction. Five groups of young offenders were compared: (a) no known child protection notifications or substantiated experience of abuse and/or neglect, (b) notifications only, (c) substantiated notifications, (d) notifications or substantiations and subsequent placement in out-of-home care (OHC), and (e) placement in OHC only. The results indicate that young people who have a history of child protection system involvement have significantly greater and more complex needs than those who have no child protection experience. It is concluded that different service responses may be required to meet the diverse needs of these groups of young people under youth justice supervision.